Analysis of Judges' Legal Considerations on the Validity of Authentic Deeds Made By a Notary - Pratama Septiandi; Amad Sudiro (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The validity of the authentic deed made by a notary/ppat is questionable. Based on this phenomenon, this study formulates the problem of how the validity of the authentic deed of sale and purchase agreement is valid and how to analyze the considerations of judges who do not accept lawsuits regarding the ratification of the authentic deed. The purpose of this study is to determine the validity and legal considerations. This research is normative juridical or research, this research uses Statute Approach and Analytical Approach. The data collection technique used is library research. Data analysis in this study uses a qualitative method. (deceased) and Soemadjoko are said to be legal (lawful) based on the Notary Deed of binding sale and purchase, dated April 25, 1995 drawn up at the Notary Office of Liana Dewi Santoso, S.H. The lawsuit was not accepted because the judge stated that there had not been a sale and purchase between Mansyur Ali (deceased) and Soemadjoko. The binding sale and purchase of land and buildings that occurred between Mansyur Ali (deceased) and Soemadjoko was said to be legal (lawful) based on the Notary Deed of binding sale and purchase, date April 25, 1995 made at the Notary Office of Liana Dewi Santoso, S.H. In the consideration of the majlis, the judge stated that the sale and purchase of land between the plaintiff and the defendant had not been carried out in accordance with the provisions of the law to the competent authority.